2021
DOI: 10.3390/molecules26113083
|View full text |Cite
|
Sign up to set email alerts
|

Doubling the Carbonate-Binding Capacity of Nanojars by the Formation of Expanded Nanojars

Abstract: Anion binding and extraction from solutions is currently a dynamic research topic in the field of supramolecular chemistry. A particularly challenging task is the extraction of anions with large hydration energies, such as the carbonate ion. Carbonate-binding complexes are also receiving increased interest due to their relevance to atmospheric CO2 fixation. Nanojars are a class of self-assembled, supramolecular coordination complexes that have been shown to bind highly hydrophilic anions and to extract even th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Supramolecular chemistry seeks to understand the rules that govern the binding of guests to hosts. Codification of this knowledge has the potential to be used in tailoring receptors for various applications, such as extraction of pollutants from water, ion regulation in batteries, and analyte sensing in water. Establishment of the rules has benefitted immensely from the creativity and design of diverse synthetic receptors . There is now a growing interest in directed approaches to design receptors, e.g., screening and selection using dynamic combinatorial chemistry or using de novo receptor design advanced with computational chemistry. This last approach relies on the use of quantitative relationships that need to be derived from the qualitative rules of host–guest chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular chemistry seeks to understand the rules that govern the binding of guests to hosts. Codification of this knowledge has the potential to be used in tailoring receptors for various applications, such as extraction of pollutants from water, ion regulation in batteries, and analyte sensing in water. Establishment of the rules has benefitted immensely from the creativity and design of diverse synthetic receptors . There is now a growing interest in directed approaches to design receptors, e.g., screening and selection using dynamic combinatorial chemistry or using de novo receptor design advanced with computational chemistry. This last approach relies on the use of quantitative relationships that need to be derived from the qualitative rules of host–guest chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Nanojars, supramolecular coordination complexes of the formula [anion⊂{ cis -Cu II (μ-OH)­(μ-pz)} n ] 2– [Cu n ; n = 26–36; pz = pyrazolate (C 3 H 3 N 2 – )], have been successfully used for the binding of oxoanions with large hydration energy such as CO 3 2– , SO 4 2– , SeO 3 2– , HPO 3 2– , HPO 4 2– , and HAsO 4 2– . Herein, we demonstrate that nanojars are excellent supramolecular binding agents not only for oxoanions but also for the fluoroanion BeF 4 2– , which was extracted from water and transferred into organic solvents (including aliphatic hydrocarbons) by liquid–liquid extraction.…”
Section: Introductionmentioning
confidence: 99%
“…4B(e) and (f)). Although many coordination hosts that can fix CO 2 by binding with carbonate have been reported, 95–102 the newly formed strong metal–oxygen interactions make these hosts unable to be reused. Thus, tube 1-Zn represents a rare coordination host that can catalyze CO 2 conversion like carbonic anhydrase.…”
Section: Resultsmentioning
confidence: 99%
“…Further experiments showed that after removal of CO 3 2encapsulated by cavity, the tube 1-Zn can be regenerated and reused (Figure 4B e-f). Although many coordination hosts that can fix CO 2 by binding with carbonate have been reported, [95][96][97][98][99][100][101][102] the new-formed strong metal-oxygen interactions make these hosts cannot be reused. Thus, tube 1-Zn represents a rare coordination host that can catalyze CO 2 conversion like carbonic anhydrase.…”
Section: Co 2 Fixation Promoted By Coordination Tubesmentioning
confidence: 99%
See 1 more Smart Citation